2017
DOI: 10.1210/js.2017-00136
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Oxytocin Neurons Causes a Deficit in Cold Stress Response

Abstract: The paraventricular nucleus (PVN) is a critical locus of energy balance control. Three sets of neurons in the PVN are involved in regulating energy balance: oxytocin-expressing neurons (OXT-neurons), thyrotropin-releasing hormone–expressing neurons, and corticotrophin-releasing hormone–expressing neurons. To examine the role of OXT-neurons in energy balance, we ablated these neurons in mice by injecting diphtheria toxin into mice possessing both the oxytocin promoter driving cre expression and a cre-inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 31 publications
1
44
0
1
Order By: Relevance
“…26,146 Oestrogen treatment has also been reported to increase oxytocin mRNA and induce anorexia in rats. 147 Among these anorexigenic substances, oxytocin has been suggested to be downstream of some anorexigenic substances to induce anorexia, including CCK, [148][149][150] Consistent with the view that oxytocin neurones are activated after food intake, ghrelin, an orexigenic hormone that is released during fasting, has been reported to hyperpolarise the majority of oxytocin neurones in the hypothalamus, 155 although i.c.v. administration of ghrelin has been reported to induce Fos protein expression in some oxytocin neurones.…”
Section: Activation Of Oxytocin Neurones By Food Intakementioning
confidence: 91%
See 2 more Smart Citations
“…26,146 Oestrogen treatment has also been reported to increase oxytocin mRNA and induce anorexia in rats. 147 Among these anorexigenic substances, oxytocin has been suggested to be downstream of some anorexigenic substances to induce anorexia, including CCK, [148][149][150] Consistent with the view that oxytocin neurones are activated after food intake, ghrelin, an orexigenic hormone that is released during fasting, has been reported to hyperpolarise the majority of oxytocin neurones in the hypothalamus, 155 although i.c.v. administration of ghrelin has been reported to induce Fos protein expression in some oxytocin neurones.…”
Section: Activation Of Oxytocin Neurones By Food Intakementioning
confidence: 91%
“…164 However, a meta-analysis revealed that the anorexigenic effect of oxytocin administration is not statistically significant in humans. 165 On the other hand, although oxytocin receptor-deficient male mice show late-onset mild obesity, 166 it has been reported that oxytocin receptor deficiency, 166 chemogenetic inhibition of hypothalamic paraventricular oxytocin neurones, 167 genetically targeted ablation of oxytocin neurones 152 and destruction of hypothalamic paraventricular oxytocin neurones 150 do not significantly change the total amounts of food intake in mice. 165 On the other hand, although oxytocin receptor-deficient male mice show late-onset mild obesity, 166 it has been reported that oxytocin receptor deficiency, 166 chemogenetic inhibition of hypothalamic paraventricular oxytocin neurones, 167 genetically targeted ablation of oxytocin neurones 152 and destruction of hypothalamic paraventricular oxytocin neurones 150 do not significantly change the total amounts of food intake in mice.…”
Section: Roles Of Oxytocin In the Control Of Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…In the PBN, we instead determined the presence of CGRP (Alhadeff, Holland, Nelson, Grill, & De Jonghe, ; Campos et al, ) in PRV‐labeled cells. The immunogen used to raise each of the antibodies used in the neurochemical phenotyping are indicated (Table ), and their specificity for the peptides is supported by citations in the literature showing their reaction in negative and positive controls (Allison et al, ; Lee et al, ; Xi et al, ; Zhang et al, ). Thus, imaging the intrinsic fluorescence of the virally encoded GFPs, cells infected with PRV‐152 appeared, and are pseudocolored, as green, those infected with PRV‐614 appeared, and were pseudocolored as magenta, while those expressing the above peptides are pseudocolored as blue.…”
Section: Methodsmentioning
confidence: 99%
“…in gray, the percentage of the dual-labeled PRV neurons. ACTH, adrenocorticotropic hormone; AP, area postrema; DMNV, dorsal motor nucleus of the vagus; E, epinephrine; GiV, gigantocellular reticular nucleus, ventral part; IML, intermediolateral nucleus; LPGi, lateral paragigantocellular nucleus; M, skeletal muscle; mlf, medial longitudinal fasciculus; n, the average total number of neurons counted in each brain region; NE, norepinephrine; NTS, nucleus of the solitary tract; PBN, parabrachial nucleus; PVN, paraventricular nucleus of the hypothalamus; ROb, raphe obscurus nucleus; RPa, raphe pallidus nucleus; SG, sympathetic chain ganglia (Allison et al, 2015;Xi et al, 2017;Zhang et al, 2003). Thus, imaging the intrinsic fluorescence of the virally encoded GFPs, cells infected with PRV-152 appeared, and are pseudocolored, as green, those infected with PRV-614 appeared, and were pseudocolored as magenta, while those expressing the above peptides are pseudocolored as blue.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%